Biomimetic interfaces for drag reduction: From mechanism to applications - Anhui Yu; Ye Fu; Shangzhen Xie; Zhiguang Guo; Feiyan Fu; Weimin Liu (Friction, 2025)
With the global population growing, energy demand has increased drastically. Simultaneously, environmental concerns have been increasing at an alarming rate. In transportation systems such as pipelines and ships, the resistance caused by friction is a major factor leading to energy loss. This not only leads to high energy consumption but also hinders improving the overall efficiency of transportation processes. Therefore, finding a solution to minimize this energy loss has emerged as a critical research area among scholars. A viable solution inspired by the unique structures in nature is deemed an effective drag reduction method. This paper outlines the bionic structures of earthworms, sharks, and dolphins and discusses their theory and mechanism for reducing drag. Furthermore, this paper compares recent approaches employing bionic drag–reduction interfaces based on earthworm, shark, and dolphin body structures. The applications of bionic interfacial drag reduction materials in agriculture, transportation, and industry are also analyzed, along with a summary of the limitations and challenges associated with bionic interfacial drag reduction. Finally, the authors look forward to future research directions and application prospects of bionic interfacial drag reduction materials.